2022
DOI: 10.1007/s12144-022-03446-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hikikomori among office workers during the COVID-19 pandemic: A prospective online survey

Abstract: The global pandemic of COVID-19 has forced people to restrict their outings. In Japan, self-restraint behavior (SRB) has been requested by the government, and some of those decreasing their outings may shift to pathological social withdrawal; hikikomori. The purpose of this study was to examine the risk factors of hikikomori conducting an online prospective survey. An online survey was conducted in June 2020 and December 2020; (1) SRB-related indicators (degree of SRB, motivation for SRB, stigma and self-stigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…In the study by Gavin and Brosnan, 35 increased time spent using digital technologies was associated with reduced symptoms of social withdrawal. This finding aligns with a study evaluating remote workers, which showed that the IAT score had a negative cross-lagged effect with the lack of socialization on the HQ-25 56 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study by Gavin and Brosnan, 35 increased time spent using digital technologies was associated with reduced symptoms of social withdrawal. This finding aligns with a study evaluating remote workers, which showed that the IAT score had a negative cross-lagged effect with the lack of socialization on the HQ-25 56 …”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns with a study evaluating remote workers, which showed that the IAT score had a negative cross-lagged effect with the lack of socialization on the HQ-25. 56 Further study is needed to clarify the role played by digital technologies in HS. The use of technologies may have beneficial effects that were not evaluated by the measures used in the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, the communication between parents and their child is often suboptimal: parents are often rejective and negative toward their child, tend to evade sensitive topics, and display indulgent behavior to avoid emotional outbursts of their offspring. Kubo et al ( 2020 , 2021 ) developed a special intervention program for parents of young people with ESW, with the aim to increase knowledge about the condition, offer tools for how best to react to their withdrawn offspring, and change malfunctional family interactions (using elements of cognitive-behavior therapy). Pilot investigations have indicated that the program has positive effects on parents’ interactive skills and supportive actions toward offspring with ESW, although it should be emphasized that the effect sizes for these changes were quite modest and certainly did not lead to a substantial improvement of young people’s withdrawal behavior.…”
Section: Interventions For Eswmentioning
confidence: 99%
“…Due to the recent COVID-19 pandemic, the Japanese government has requested citizens to selfrestraint. People may shift to pathologically social withdrawal, known as Hikikomori (Kubo et al, 2022). The rise of this phenomenon in Japanese news, especially NHK (Nippon Hoso Kyokai -Japan Broadcasting Corporation) website addressed concerns among citizens and government.…”
Section: Introductionmentioning
confidence: 99%